PC.26 Feasibility of Magnetic Resonance Spectroscopy in Examining Thalamic Metabolite Concentrations in a Multi-Centre Study of Neonatal Encephalopathy. (9th June 2014) - Lally, PJ; Price, DL; Bainbridge, A; Pauliah, SS; Satodia, P; Wayte, SC; Abernethy, L; Turner, M; Basheer, AN; Alavi, A; Kirmi, O; Jones, B; et al.
Abstract : Background: Proton magnetic resonance spectroscopy (MRS) has high prognostic value in hypoxic ischaemic encephalopathy (HIE), however its multi-centre application is limited by inconsistencies between scanners and protocols. N-acetylaspartate (NAA) is predominantly neuronal: cerebral NAA concentration may be a more reliable HIE-severity biomarker than lactate/NAA. Objective: To quantify the inter-site and inter-subject variability of NAA concentration measurements. Design/Methods: We recruited 5 healthy adult volunteers (aged 24–38, 2 male, 3 female) whom we scanned at 3 UK sites participating in a multi-centre neonatal-brain study (University Hospital, Coventry (UHC); Alder Hey Children's Hospital, Liverpool (AH); University College Hospital, London (UCLH)). Thalamic NAA concentration was measured using the neonatal brain-water concentration reference protocol (15 × 15 × 15mm 3 voxel; PRESS; water-suppressed TR/TE = 2s/288&60ms; TR/TE = 5s/60ms; non-water-suppressed TR = 10s, TE = 60/124/205/316/495/1000 ms). Spectra were post-processed in jMRUI and metabolites fitted with LCModel. Results: One volunteer was unavailable for scanning at AH. The mean (SD) NAA concentrations across the remaining four subjects were 15.5(3.4)mmol/kg wet weight, 14.4(0.1) mmol/kg wet weight, and 15.2(0.1) mmol/kg wet weight at UHC, AH and UCLH respectively. This corresponds to a maximum inter-site group mean variation (range/mean) of 8%. The inter-subject variability of mean NAA concentration (SD/mean) was 10%. Conclusions: The variation of thalamic NAA concentration between sites was 8% and the standard deviation across subjects was 10%, hence [NAA] may be suitable for multi-centre studies.